2018
DOI: 10.3758/s13428-018-1074-z
|View full text |Cite
|
Sign up to set email alerts
|

A gaze interactive assembly instruction with pupillometric recording

Abstract: This paper presents a study of a gaze interactive digital assembly instruction that provides concurrent logging of pupil data in a realistic task setting. The instruction allows hands-free gaze dwells as a substitute for finger clicks, and supports image rotation as well as image zooming by head movements. A user study in two LEGO toy stores with 72 children showed it to be immediately usable by 64 of them. Data logging of view-times and pupil dilations was possible for 59 participants. On average, the childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Old reflection-based methods face challenges when applied in real-world settings because they require dedicated NIR devices. These methods are majorly subject to eye occlusion, and other reflection irregularities, such as pupil dilation [19,153,154]. To solve these bottlenecks, recent attempts by researchers have been based on techniques which focus on image appearance to extract the characteristics of the entire eye region instead of specific features that require a dedicated device [155].…”
Section: Appearance-based Methodsmentioning
confidence: 99%
“…Old reflection-based methods face challenges when applied in real-world settings because they require dedicated NIR devices. These methods are majorly subject to eye occlusion, and other reflection irregularities, such as pupil dilation [19,153,154]. To solve these bottlenecks, recent attempts by researchers have been based on techniques which focus on image appearance to extract the characteristics of the entire eye region instead of specific features that require a dedicated device [155].…”
Section: Appearance-based Methodsmentioning
confidence: 99%
“…Recent studies by Čegovnik et al (2018) and Hansen et al (2018) has found that even a low-cost 30 Hz remote gaze tracker may provide reliable pupil measures that corresponds well with changes in task load during simulated driving and assembling of construction toy, respectively.…”
Section: Previous Workmentioning
confidence: 96%
“…Then, the external world may not only provide the challenge (e.g., the search display), but also ease the challenge, by allowing to resample the template. Indeed, during many tasks, humans look back and forth at instructions in order to help them succeed ( Hayhoe, Shrivastava, Mruczek, & Pelz, 2003 ; Droll & Hayhoe, 2007 ; Hansen, Mardanbegi, Biermann, & Bækgaard, 2018 ; Alfandari, Belopolsky, & Olivers, 2019 ; Sullivan, Ludwig, Damen, Mayol-Cuevas, & Gilchrist, 2021 ). This behavior is in line with earlier findings on mental effort and memory, which indicate that offloading memory is preferred as much as possible over storing internally, by (re)sampling from the environment in a just-in-time manner ( O’Regan, 1992 ; Hayhoe et al., 2003 ; Triesch, Ballard, Hayhoe, & Sullivan, 2003 ; Droll, Hayhoe, Triesch, & Sullivan, 2005 ; Risko & Dunn, 2015 ; Risko & Gilbert, 2016 ; Melnik, Schüler, Rothkopf, & König, 2018 ; Somai, Schut, & Van der Stigchel, 2020 ; Van der Stigchel, 2020 ; Draschkow, Kallmayer, & Nobre, 2021 ).…”
Section: Introductionmentioning
confidence: 99%